2012
DOI: 10.1186/1743-422x-9-287
|View full text |Cite
|
Sign up to set email alerts
|

A serological survey of human adenovirus serotype 2 and 5 circulating pediatric populations in Changchun, China, 2011

Abstract: BackgroundEfficacy of recombinant adenovirus serotype 5 (rAd5) vaccine vectors for human immunodeficiency virus type 1 (HIV-1) and other pathogens have been shown to be limited by high titers of pre-existing Ad5 neutralizing antibodies (NAbs) in the developing world.ResultsUsing a secreted embryonic alkaline phosphatase (SEAP) neutralization assay, 50% serum neutralization titers against rAd2 and rAd5 vectors were measured in samples from 274 infants and young children in northeast China. The pediatric populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
2
20
0
2
Order By: Relevance
“…Nevertheless, a potential target population for an Ad5-vectored RSV vaccine still exists among infants 4 to 23 months old who present with limited adenoviral preformed active immunity (since Ad5 infections are uncommon early in life) and who have little or no passive immunity (since infants in this age group have already lost most or all of the anti-Ad5 antibodies acquired from their mothers) (17,18). The seroprevalence of human adenovirus serotypes 2 and 5 circulating in different age groups supports the knowledge that antiadenoviral neutralizing immunity is present in newborns and tends to decline after 6 months of age (19). Thus, recombinant adenovirus may represent an excellent platform for vaccines against RSV and other members of the paramyxoviridae (human parainfluenza virus type 1 [hPIV1] to hPIV4, metapneumovirus) within this young pediatric population.…”
supporting
confidence: 54%
“…Nevertheless, a potential target population for an Ad5-vectored RSV vaccine still exists among infants 4 to 23 months old who present with limited adenoviral preformed active immunity (since Ad5 infections are uncommon early in life) and who have little or no passive immunity (since infants in this age group have already lost most or all of the anti-Ad5 antibodies acquired from their mothers) (17,18). The seroprevalence of human adenovirus serotypes 2 and 5 circulating in different age groups supports the knowledge that antiadenoviral neutralizing immunity is present in newborns and tends to decline after 6 months of age (19). Thus, recombinant adenovirus may represent an excellent platform for vaccines against RSV and other members of the paramyxoviridae (human parainfluenza virus type 1 [hPIV1] to hPIV4, metapneumovirus) within this young pediatric population.…”
supporting
confidence: 54%
“…Moderate prevalence of low level Ad NAb in infants less than 6 months of age was commonly detected in prior reports [22,28,33,34], which was attributed to maternal antibodies. Because of the very limited sample size for the group of <6 months of age, it was combined to neighboring groups and was not separately analyzed in this study.…”
Section: Discussionmentioning
confidence: 73%
“…Infants aged 6-12 months tend to have low titers, which then steadily increase. 40 A study conducted in India showed that neutralizing antibodies to HAdV-5 virus are slightly higher in infants aged 1-6 months than aged 7-12 months. Titers then steadily increase until adulthood.…”
Section: Preexisting Immunity To Antigen Of Adenovirusesmentioning
confidence: 99%